(untitled) (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
Technological advancements, particularly the widespread penetration of smartphones, have substantially accelerated the adoption of digital payment systems across both formal and informal segments of the economy. This shift towards electronic transactions has emerged as a critical driver of financial inclusion by enabling broader access to formal financial services. The present study investigates the impact of digital payment adoption on participants within the informal economy—specifically vegetable vendors, small retail shop owners, street vendors, and pan parlour operators—in the Sabarkantha district of Gujarat. Research Purpose: This study evaluates the socio-economic and systemic determinants facilitating the transition from traditional paper-based transactions to Fintech-driven paperless systems within the informal economic sector of the Sabarkantha district of Gujarat. It specifically examines how demographic variables influence the perception of legal, social, and technological risks. Research Methodology: A quantitative approach was employed, utilizing a structured survey administered to 211 participants in the Sabarkantha region. Data were analyzed using Descriptive Statistics, Independent Samples T-tests, One-Way ANOVA, and Spearman’s Rho Correlation to test the relationships between demographic factors and digital payment adoption. Findings: The analysis reveals that while the transition is accelerated by younger demographics (64% aged 18–45), it is significantly moderated by education (p=0.003) and income level (p=0.003). Furthermore, a strong correlation exists between economic benefits and E-payment preference (rho value = 0.406); however, "Unsafe Technology" remains a significant psychological barrier to full-scale digital integration. The findings underscore that while technological innovation plays a pivotal role in transforming economic transactions, ensuring robust data protection mechanisms and enhancing digital literacy are essential for sustaining trust and promoting inclusive growth across informal economic sectors. Originality/Value: This research contributes to the "Digital Financial Inclusion" discourse by identifying the specific socio-economic friction points that impede the "Paper to Paperless" journey in emerging informal markets.